Liquidity Choice and Misallocation of Credit - Ebrahimy, Ehsan (IMF Working Papers; Working Paper ;, 2019)
This paper studies a novel type of misallocation of credit between investments of varying liquidity. One type of investment is more liquid, id est, its return is more pledgeable, and the other is more productive. Low liquidities of both investment types imply that the allocation of credit is constrained inefficient and that there is overinvestment in the liquid type. Constrained inefficient equilibria feature non-positive, id est, one less than or equal the economy's growth rate, and yet too high interest rate, too much investment and too little consumption. Financial development can reduce long-term welfare and output in a constrained inefficient equilibrium if it raises the liquidity of the liquid type. I show a maximum liquid asset ratio or a simple debt tax can achieve constrained efficiency. Introducing government bonds can make Pareto improvement whenever it does not raise the interest rate.